All integers are in a row.

Let n > 1 n > 1 be a positive integer. Each cell of an n × n n \times n table contains an integer.Suppose that the following conditions are satisfied: \\ ( i ) (i) Each number in the table is congruent to 1 1 modulo n n ; \\ ( i i ) (ii) The sum of numbers in any row, as well as the sum of numbers in any column, is congruent to n n modulo n 2 n^2 .

Let R i R_i be the product of the numbers in the i t h i^{th} row, and C j C_j be the product of the numbers in the j t h j^{th} column.

Find the largest possible integer N N such that the statement

the sums i = 1 n R i \displaystyle \sum _{ i=1 }^{ n } { R_i } and i = 1 n C i \displaystyle \sum _{ i=1 }^{ n }{ { C }_{ i } } are congruent to each other modulo N N

is always true.

n 4 n^4 n 8 n^8 n 2 n^2 n 3 n^3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jul 28, 2019

The case n = 2 n=2 is best handled separately. The matrix of elements must be of the form ( 1 + 2 a 1 2 a + 4 b 1 2 a + 4 c 1 + 2 a + 4 d ) \left(\begin{array}{cc} 1 +2a & 1 - 2a + 4b \\ 1 - 2a + 4c & 1 + 2a + 4d \end{array}\right) for integers a , b , c , d a,b,c,d , and it is easy to calculate that ( R 1 + R 2 ) ( C 1 + C 2 ) = 16 ( c b ) d (R_1+R_2)-(C_1+C_2) = 16(c-b)d is always a multiple of 16 16 , but not necessarily a multiple of 32 32 .


Suppose now that n 3 n \ge 3 . We can write the elements of the matrix as a i j = 1 + n b i j 1 i , j n a_{ij} \; = \; 1 + nb_{ij} \hspace{2cm} 1 \le i,j \le n where b i j b_{ij} are integers. We also must have integers α i , β i \alpha_i,\beta_i for 1 i n 1 \le i \le n such that j = 1 n b i j = n α i j = 1 n b j i = n β i 1 i n \sum_{j=1}^n b_{ij} \; = \; n\alpha_i \hspace{1cm} \sum_{j=1}^n b_{ji} \; = \; n\beta_i \hspace{2cm} 1 \le i \le n

Let us define the quantities B k = i j b i j k k N B_k \; = \; \sum_{ij}b_{ij}^k \hspace{2cm} k \in \mathbb{N} as well as X 1 i = j 1 < j 2 b i j 1 b i j 2 X 2 j = i 1 < i 2 b i 1 j b i 2 j Y 1 i = j 1 < j 2 < j 3 b i j 1 b i j 2 b i j 3 Z 2 j = i 1 < i 2 < i 3 b i 1 j b i 2 j b i 3 j \begin{array}{rclcrcl} X_{1i} & \; =\; & {\displaystyle \sum_{j_1<j_2}b_{ij_1}b_{ij_2}} & & X_{2j} & \; = \; & {\displaystyle \sum_{i_1 < i_2}b_{i_1j}b_{i_2j}} \\ Y_{1i} & \;=\; & {\displaystyle \sum_{j_1<j_2<j_3}b_{ij_1}b_{ij_2}b_{ij_3}} & & Z_{2j} & \; =\; & {\displaystyle \sum_{i_1<i_2<i_3}b_{i_1j}b_{i_2j}b_{i_3j}} \end{array}


First note that n i α i = B 1 = n j β j n\sum_i\alpha_i \; = \; B_1 \; = \; n\sum_j\beta_j so that Q = j ( α j 2 β j 2 ) = 2 i < j ( β i β j α i α j ) Q \; = \; \sum_j(\alpha_j^2 - \beta_j^2) \; = \; 2\sum_{i<j}(\beta_i\beta_j - \alpha_i\alpha_j) is even. But then 2 X 1 i = = j 1 j 2 b i j 1 b i j 2 = ( j b i j ) 2 j b i j 2 = n 2 α i 2 j b i j 2 2X_{1i} \; = \; \; = \; \sum_{j_1 \neq j_2}b_{ij_1}b_{ij_2} \; = \; \left(\sum_jb_{ij}\right)^2 - \sum_jb_{ij}^2 \; = \; n^2\alpha_i^2 - \sum_jb_{ij}^2 so that 2 i X 1 i = n 2 i α i 2 B 2 2\sum_iX_{1i} \; = \; n^2 \sum_i\alpha_i^2 - B_2 Similarly 2 j X 2 j = n 2 j β j 2 B 2 2\sum_jX_{2j} \; = \; n^2\sum_j\beta_j^2 - B_2 and hence 2 i X 1 i 2 j X 2 j = Q n 2 2\sum_iX_{1i} - 2\sum_jX_{2j} \; = \; Qn^2 so that i X 1 i j X 2 j ( m o d n 2 ) \sum_iX_{1i} \; \equiv \; \sum_jX_{2j} \hspace{2cm} (\mathrm{mod}\; n^2)


Next note that ( j b i j ) 3 = j b i j 3 + 3 j 1 j 2 b i j 1 2 b i j 2 + 6 Y 1 i = 2 j b i j 3 + 3 ( j b i j 2 ) ( j b i j ) + 6 Y 1 i = 2 j b i j 3 + 3 ( j b i j ) 3 6 ( j 1 < j 2 b i j 1 b i j 2 ) ( j b i j ) + 6 Y 1 i 3 Y 1 i = i b i j 3 n 3 α i 3 + 3 n α i X 1 i \begin{aligned} \left(\sum_jb_{ij}\right)^3 & = \; \sum_jb_{ij}^3 + 3\sum_{j_1 \neq j_2}b_{ij_1}^2b_{ij_2} + 6Y_{1i} \\ & = \; -2\sum_j b_{ij}^3 + 3\left(\sum_jb_{ij}^2\right)\left(\sum_jb_{ij}\right) + 6Y_{1i} \\ & = \; -2\sum_j b_{ij}^3 + 3\left(\sum_j b_{ij}\right)^3 - 6\left(\sum_{j_1<j_2}b_{ij_1}b_{ij_2}\right)\left(\sum_jb_{ij}\right) + 6Y_{1i} \\ 3Y_{1i} & = \; \sum_ib_{ij}^3 - n^3\alpha_i^3 + 3n\alpha_iX_{1i} \end{aligned} so that 3 i Y 1 i = B 3 n 3 i α i 3 + 3 n i α i X 1 i 3\sum_iY_{1i} \; = \; B_3 - n^3\sum_i\alpha_i^3 + 3n\sum_i\alpha_iX_{1i} Similarly 3 j Y 2 j = B 3 n 3 j β j 3 + 3 n j β j X 2 j 3\sum_jY_{2j} \; = \; B_3 - n^3\sum_j\beta_j^3 + 3n\sum_j\beta_jX_{2j} and hence 3 ( i Y 1 i j Y 2 j ) = n 3 j ( β j 3 α j 3 ) + 3 n j ( α j X 1 j β j X 2 j ) 3\left(\sum_iY_{1i} - \sum_jY_{2j}\right) \; = \; n^3\sum_j(\beta_j^3 - \alpha_j^3) + 3n\sum_j(\alpha_jX_{1j} - \beta_jX_{2j}) from which it is clear that i Y 1 i j Y 2 j ( m o d n ) \sum_iY_{1i} \; \equiv \; \sum_jY_{2j} \hspace{2cm} (\mathrm{mod}\; n) even when n n is divisible by 3 3 .


We now note that R i = j a i j = j ( 1 + n b i j ) 1 + n j b i j + n 2 X 1 j + n 3 Y 1 i ( m o d n 4 ) R_i \; = \; \prod_ja_{ij} \; = \; \prod_j(1 + nb_{ij}) \equiv \; 1 + n\sum_jb_{ij} + n^2X_{1j} +n^3Y_{1i} \hspace{2cm}(\mathrm{mod}\; n^4) so that i R i = n + n B 1 + n 2 i X 1 i + n 3 i Y 1 i ( m o d n 4 ) \sum_i R_i \; = \; n + nB_1 + n^2\sum_iX_{1i} + n^3\sum_iY_{1i} \hspace{2cm} (\mathrm{mod}\;n^4) Similarly j C j = n + n B 1 + n 2 j X 2 j + n 3 j Y 2 j ( m o d n 4 ) \sum_j C_j \; = \; n + nB_1 + n^2\sum_jX_{2j} + n^3\sum_jY_{2j} \hspace{2cm} (\mathrm{mod}\;n^4) and hence we deduce that i R i j C j ( m o d n 4 ) \sum_i R_i \; \equiv \; \sum_j C_j \hspace{2cm} (\mathrm{mod}\;n^4)

Thus i R i \sum_iR_i and j C j \sum_jC_j are congruent modulo n 4 n^4 for any integer n 2 n \ge 2 . Since the two quantities are not always congruent modulo n 5 n^5 , as can be seen by the n = 2 n=2 case, we see that the correct answer is n 4 \boxed{n^4} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...